O project finance no financiamento de empreendimentos em saneamento básico no Brasil - Fontes, Carlos Henrique Queiroga e (2002)
The current situation of the water and sewage utilities' systems in Brazil, as well as the regulatory and institutional frame of the sector, are the result of disturbed antecedents and discontinuous politics, determined by situational aspects and by the altemation between greater and smaller readiness of financiaI resources. The privatization and the concession of services offers concrete perspectives ofredefinition ofthe path of evolution ofthe sector, with the establishment of a more constant and regular pattem of growth of the covering indexes and of modemization of the systems as well as of the management techniques. The private investment's logic implicates in orientation for the profit and in the configuration of structures of smaller risk for the committed financiaI resources with the enterprise. The project finance is a financing technique that allows the partition of risks among the participants, reducing individual portions and, consequently, joining larger attractiveness to the business. The aim of the present study is to analyze the water and sewage utilities' sector and the project finance, looking for to identify the possibilities and the presumably impacts of the introduction and diffusion of the technique as financing altemative for the sector in Brazil.